Analysis of Traffic Accident-Prone Locations (Case Study: Kaliurang Road, Sleman Regency) - Halim, Muhammad Farid Halim; Sugianto, Sugianto; Hardimansyah, Rizki (Journal of Green Science and Technology, 2025)
Traffic accidents are one of the leading causes of high mortality rates in Indonesia. During the period 2022–2024, Kaliurang Road in Sleman Regency was identified as one of the road segments with a high accident rate, with a total of 359 incidents resulting in 24 fatalities and 451 minor injuries. This study aims to identify accident-prone locations along the Kaliurang Road segment. The methods used include the Equivalent Accident Number (EAN) to weight accident severity levels, as well as the Upper Control Limit (UCL) and Upper Control Boundary (BKA) methods to determine accident-prone locations. The analysis of traffic accident characteristics shows that most incidents occurred in the morning (06:00–12:00), with male drivers being the most frequent offenders and motorcycles being the most commonly involved vehicle type. The most dominant collision type was a crash between the front and side parts of vehicles. Four accident-prone segments were identified: kilometers 7–8, 8–9, 12–13, and 13–14. Recommendations for addressing these accident-prone locations include the installation of rumble strips, rearrangement of community activity spaces or roadside obstruction control, improvement of street lighting, enhancement of road markings and warning signs, and the provision and installation of appropriate traffic signs. This study provides recommendations by identifying accident-prone locations along Kaliurang Road and offering suggestions based on accident characteristics and road conditions to improve traffic safety for road users.